2008
DOI: 10.1245/s10434-008-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hepatic Resection Margin on Recurrence and Survival in Intrahepatic Cholangiocarcinoma

Abstract: Hepatic resection margin seems to play a minor role in the prognosis of ICC as long as complete tumor clearance can be achieved with a modern liver dissection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
144
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(160 citation statements)
references
References 26 publications
12
144
3
1
Order By: Relevance
“…However, a recent meta-analysis pointed out that the failure to identify any impact of tumor size on OS could be explained by the limited number of patients with small tumors (,5 cm) included in previously studies [21]. Furthermore, more factors were probably involved that would affect the prognosis of ICC after liver resection, and the role of these additional risk variables, in addition to the TNM factors, should be further studied [22][23][24]. Recently, we reported a prognostic nomogram for ICC patients who underwent partial hepatectomy [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis pointed out that the failure to identify any impact of tumor size on OS could be explained by the limited number of patients with small tumors (,5 cm) included in previously studies [21]. Furthermore, more factors were probably involved that would affect the prognosis of ICC after liver resection, and the role of these additional risk variables, in addition to the TNM factors, should be further studied [22][23][24]. Recently, we reported a prognostic nomogram for ICC patients who underwent partial hepatectomy [7].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with resection generally have the higher recurrence rate. 43,44 In addition, chemotherapy also induces acquired resistance that has been one of the most important clinical problems. 45,46 At such a circumstance, there is now a real and urgent need to focus on developing novel therapeutic strategies for cholangiocarcinoma that would impact in a significant way on clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a small number of patients, extended LN dissection has enhanced the long-term survival after curative surgical treatment [18]. Conversely, some investigators have suggested that patients with LN metastasis should not be considered suitable candidates for extended surgical treatment, because most LN metastases were detected at a great distance from the regional area [19][20][21][22]. Moreover, there is no evidence of the significance of LN dissection based on a definitive controlled study.…”
Section: Introductionmentioning
confidence: 99%